2020
DOI: 10.3390/en13226016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Long-Term Investigation of Model Predictive Heat Pump Control in Residential Buildings with Photovoltaic Power Generation

Abstract: This article presents a 125-day experiment to investigate model predictive heat pump control. The experiment was performed in two parallel operated systems with identical components during the heating season. One of the systems was operated by a standard controller and thus represented a reference to evaluate the model predictive control. Both test rigs were heated by an air-source heat pump which is influenced by real weather conditions. A single-family house model depending on weather measurement data ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Additionally, the application of MPC resulted in a remarkable reduction of operational costs by 34.0%. In a separate long-term investigation presented in [7], the authors evaluated the MPC HP control in a residential building with PV power generation over a 135-day experiment. The study demonstrated that the electrical energy demand of the heat pump can be reduced, leading to an enhanced coefficient of performance.…”
Section: Control Approaches In Thermal-electrical Systemsmentioning
confidence: 99%
“…Additionally, the application of MPC resulted in a remarkable reduction of operational costs by 34.0%. In a separate long-term investigation presented in [7], the authors evaluated the MPC HP control in a residential building with PV power generation over a 135-day experiment. The study demonstrated that the electrical energy demand of the heat pump can be reduced, leading to an enhanced coefficient of performance.…”
Section: Control Approaches In Thermal-electrical Systemsmentioning
confidence: 99%
“…This poses another technical challenge due to the varying weather conditions and user profiles. Therefore, to ensure identical boundary conditions and external input parameters as much as possible, many experimental comparison studies have taken place in controlled laboratory environments, such as a 125-day experiment on MPC for heat pumps in a single-family house lab environment showing a 9% cost reduction in comparison to a conventional controller [17]. Further experimental studies in lab environments can be found in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies discuss many innovative clean energy technologies [27], which could be used in renovation of residential houses in order to improve their energy efficiency. Research on the use of different systems based on renewable energy, including the experimental investigations on heat pumps driven by PV systems in SFH have been rising in importance and popularity [28,29]. Such studies regarding SFH in Poland's climatic conditions show the applications of this renewable energy technology after thermal modernization of SFH can be cost effective and recommended [28].…”
Section: Introductionmentioning
confidence: 99%